Genetic diversity and community composition of arbuscular mycorrhizal fungi associated with root and rhizosphere soil of the pioneer plant Pueraria phaseoloides. Issue 4 (30th September 2022) - Guo, Yaqin; Bei, Qicheng; Dzomeku, Beloved Mensah; Martin, Konrad; Rasche, Frank
Abstract : The pioneering plant Pueraria phaseoloides had a strong modulation effect on arbuscular mycorrhizal fungi (AMF) communities. Irrespective of geographical location, community composition of AMF in rhizosphere soil differed from that of the root. Co‐occurrence network analysis revealed two AMF keystone species in rhizosphere soil ( Acaulospora ) and roots ( Rhizophagus ) of P. phaseoloides .